The Heliospheric Meteorology Mission: A Mission to DRIVE our Understanding of Heliospheric Variability - McIntosh, Scott W.; Leamon, Robert J. (Frontiers in Astronomy and Space Sciences, 2018)
To make transformational scientific progress with the space weather enterprise the Sun, Earth, and heliosphere must be studied as a coupled system, comprehensively. Rapid advances were made in the study, and forecasting, of terrestrial meteorology half a century ago that accompanied the dawn of earth observing satellites. Those assets provided a global perspective on the Earthâs weather systems and the ability to look ahead of the observerâs local time. From a heliospheric, or space, weather perspective we have the same fundamental limitation as the terrestrial meteorologists had \-- by far the majority of our observing assets are tied to the Sun-Earth line \-- our planetâs ``local time'' with respect to the Sun. This perspective intrinsically limits our ability to ``see what is coming around the solar limb'' far less to gain any insight into the global patterns of solar weather and how they guide weather throughout the heliosphere. We propose a mission concept \-- the Heliospheric Meteorology Mission (HMM) \-- to sample the complete magnetic and thermodynamic state of the heliosphere inside 1AU using a distributed network of deep space hardened smallsats that encompass the Sun. The observations and in situ plasma measurements made by the fleet of HMM smallsats would be collected, and assimilated into current operational space weather models. Further, the HMM measurements would also being used in an nationally coordinated research effort - at the frontier of understanding the coupled heliospheric system.